THE IMPORTANCE OF EDUCATION - Eshpulatova Sevinch (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This research provides an extensive analysis of the multifaceted role of education in modern civilization. It explores education as a primary driver of human rights, socio-economic mobility, and psychological well-being. The study moves beyond the traditional view of schooling to examine how lifelong learning and intellectual capital shape the geopolitical and cultural landscape of the twenty-first century